Family welfare: Relationship with gender roles and wife's income - Hasyim, Fuad; Salim, Agus; Yuanita, Yuanita; Bahren, Bahren (UIN Ar-Raniry Banda Aceh, 2026)
The family represents the smallest unit within a society or a nation, generally consisting of parents and children whose marital status is legally recognized. Within the family structure, roles and responsibilities are distributed based on gender. This division of tasks aims to support the overall achievement of the family’s goals. This study investigates the negotiation of gender roles and economic welfare within dual-earner families, specifically analyzing how disproportionate female income contributions correlate with domestic task distribution and household prosperity levels. This research employed a survey method with a sample of 85 dual-earner families randomly selected from a total population of 109 families. The collected data were analyzed using descriptive quantitative methods and statistically tested with the Fisher Exact Test. The results indicate that domestic responsibilities are predominantly handled by wives, while public or social activities are performed jointly by both husbands and wives. Moreover, in 96.4% of the families, more than half of the total household income comes from the wives’ earnings. The majority of families, totaling 80 households (94.2%), are classified as first-level prosperous families, while the remaining 5 families (5.8%) fall into the pre-prosperous category. According to the World Bank classification, 3 families (3.6%) are in the extreme poverty category, 65 families (76.4%) are in the lower-middle-income group, and 17 families (20%) are categorized as upper-middle-income.